PERLINDUNGAN HUKUM BAGI KONSUMEN PRODUK PANGAN DALAM KEMASAN TANPA LABEL HALAL PADA USAHA KECIL (Magister Hukum Universitas HKBP Nommensen, 2022)
The main problem in this research is how legal protection is for consumers of packaged food products without halal labels in small businesses. This research aims to find out how halal-labeled food products are regulated in relation to consumer protection, and what legal efforts consumers can take to obtain protection for their rights. The research method used in the research is normative law with a statutory approach and a conceptual approach. Information is obtained from primary legal materials, secondary legal materials and non-legal materials. As for legal materials, both primary legal materials, secondary legal materials and non-legal materials are described and connected in such a way, so that they are presented in more systematic writing to answer the problems that have been formulated. From the results of the research above, it can be concluded that the obligations that must be carried out and carried out by business actors, especially small businesses. to include a halal label on the packaging of every product produced in accordance with Article 8 Paragraph (1) letter h UUPK, and legal remedies that consumers can take in accordance with UUPK, namely, can resolve disputes directly with business actors, complaints through YLKI, Settlement through BPOM, report to BPSK and resolve through the General Court.